Attachment & Loneliness: Study of First-Time Adult Women Experiencing Parental Divorce - Masbul, Hajrah Rizkiyani; Ninin, Retno Hanggarani (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study is aimed at investigate the role of attachment to loneliness for early adult children in experiencing parental divorce. Qualitative research was used. The population in this study were all girls whose parents experienced divorce. The sampling technique uses incidental sampling. The sample for this study consisted of 104 children aged 18-25 years. The primary data in this study were teenage children who had experience of their parents' divorce. Research data was obtained from teenagers and adults through interviews. The data analysis technique used in this research is quantitative-descriptive analysis. The results of this finding found that there was an effect of attachment to loneliness of early adult female experiencing parental divorce. Additional analysis of the type of attachement was carried out in this study using Relationship Quistionnaire (RQ), discovered that fearful subject’s has the high correlation. There was a difference between the father-attachment and the mother-attachment. Furthermore, age at the time of the divorce it is found to be associated with loneliness as an adult.